EVOLUTION OF STELLAR MODELS WITH HIGH METAL CONTENT - TORRES PEIMBERT, S (UNAM, Boletín de Observatorios Tonatzintla y Tacubaya, México., 1971)
Evolutionary sequences for stellar configurations between 1 and 1.45 /b M//sub o/ with chemical abundances varying from /b Z/=0.023 to 0.10 and from /b X/=0.60 to 0.68 were computed using the Berkeley Stellar Evolution program. The effect of high metal ab
BOL OBS TONAN TACUB
Keywords: EVOLUTION, STELLAR, MODELS, HIGH, METAL CONTENT; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS